THE DESCRIPTION OF THE KNOWLEDGE, ATTITUDE AND PREVENTIVE OF SEXUALLY TRANSMITTED DISEASES (STDS) ON COMMERCIAL SEX WORKERS (CSWS) AT BALONG CANGKRING MOJOKERTO - Mardiyana, Rina; Maria Ulfa, Dina (JURNAL KEPERAWATAN SEHAT, 2016)
Sexually Transmitted Diseases (STDs) are diseases that can be transmitted person to another through sexual intercourse. One group of women who experienced a range of sexually transmitted diseases is commercial sex workers (CSWs ), it takes knowledge, attitudes and actions both on the prostitutes to prevent the transmission of infectious diseases seksual. The description of the knowledge, attitude and preventive of sexually transmitted diseases (STDs) on commercial sex workers (CSWs). This study used a descriptive design. The population in this study were all female commercial sex workers in Mojokerto Balongcangkring Localization of 60 respondents. A sample of 60 respondents were taken using total sampling. Data sources using primary data, instrument data collection using questionnaires and how to capture data through questionnaires. Results of the study are presented in the form of a frequency distribution table. The result showed nearly half of the respondents have good knowledge about the prevention of sexually transmitted diseases as many as 23 respondents (38.3%), have a positive attitude about the prevention of sexually transmitted diseases as many as 29 respondents (48.3%) and the majority of respondents negative action on prevention of sexually transmitted diseases as many as 38 respondents (63.3%). The results showed that the psychomotor domain or action / real behavior of infectious disease prevention is more dominant negative than the previous domain knowledge and attitudes. The actions of the respondents are still many negative and remained localized is heavily influenced by several things, either personal reasons or general reasons, and the most powerful reason is the economic reasons on which they are very difficult to find a job with a decent income but it also identified that revenues they are also less than UMK Mojokerto (Rp.2.695.000), with a revenue number was considered very less.Keywords: Sexually Transmitted Diseases (STDs), Knowledge, Attitude, Action